The solution consists of two parts:
"f(t)=f_{hom}(t)+f_{par}(t)\\\\[0.3cm]\nf_{hom}(t)-\\text{solution of a homogeneous equation}\\\\[0.3cm]\n2f''(t)-3f'(t)+f(t)=0\\\\\nf_{par}(t)-\\text{particular solution of an inhomogeneous equation}\\\\[0.3cm]\n2f''(t)-3f'(t)+f(t)=t\\cdot e^t"
1 STEP: We solve the homogeneous equation
"2f''(t)-3f'(t)+f(t)=0"
We will seek a solution in the form "f(t)=e^{kt}" , then
"f(t)=e^{kt}\\longrightarrow\n\\left\\{\\begin{array}{l}\nf'(t)=k\\cdot e^{kt}\\\\[0.3cm]\nf''(t)=k^2\\cdot e^{kt}\n\\end{array}\\right.\\longrightarrow\\\\[0.3cm]\n2\\cdot k^2\\cdot e^{kt}-3\\cdot k\\cdot e^{kt}+e^{kt}=0\\\\[0.3cm]\ne^{kt}\\cdot\\left(2k^2-3k+1\\right)=0\\longrightarrow\\underbrace{2k^2-3k+1=0}_{\\text{quadratic equation}}\\\\[0.3cm]\n\\sqrt{D}=\\sqrt{\\left(-3\\right)^2-4\\cdot 2\\cdot1}=\\sqrt{1}=1\\\\[0.3cm]\n\\left[\\begin{array}{l}\nk_1=\\displaystyle\\frac{-(-3)+1}{2\\cdot2}=1\\\\[0.3cm]\nk_2=\\displaystyle\\frac{-(-3)-1}{2\\cdot2}=\\displaystyle\\frac{1}{2}\n\\end{array}\\right.\\\\[0.3cm]\n\\boxed{f_{hom}(t)=C_1\\cdot e^t+C_2\\cdot e^{t\/2}}"
2 STEP: We solve the inhomogeneous equation
"2f''(t)-3f'(t)+f(t)=t\\cdot e^t"
Minimum required theory: when solving inhomogeneous equations of the form
"F\\left(f,f',f'',f''',\\ldots\\right)=g(t)"
if the right side is "g(t)=P_m(t)\\cdot e^{\\alpha t},\\,\\,\\text{where}\\,\\,\\, P_m(t)-\\text{polynomial}" , then to look for the particular solution in the form
"\\left[\\begin{array}{l}\n\\widetilde{P_m}(t)\\cdot e^{\\alpha t}-\\alpha\\,\\,\\text{not the root of the characteristic equation}\\\\[0.3cm]\nx^s\\widetilde{P_m}(t)\\cdot e^{\\alpha t}-\\alpha\\,\\,\\text{the root of the characteristic equation}\n\\end{array}\\right."
In our case,
"g(t)=t\\cdot e^{1\\cdot t}\\longrightarrow k_1=1-\\text{multiplicity root 1}\\\\[0.3cm]\nf_{par}(t)=t\\cdot\\left(At+B\\right)\\cdot e^t\\equiv\\left(At^2+Bt\\right)\\cdot e^t\\longrightarrow\\\\[0.3cm]\n\\left\\{\\begin{array}{l}\nf'(t)=\\left(At^2+Bt\\right)\\cdot e^t+\\left(2At+B\\right)\\cdot e^t\\\\[0.3cm]\nf'(t)=\\left(At^2+(2A+B)t+B\\right)\\cdot e^t\\\\[0.3cm]\nf''(t)=\\left(At^2+(2A+B)t+B\\right)\\cdot e^t+\\left(2At+(2A+B)\\right)\\cdot e^t\\\\[0.3cm]\nf''(t)=\\left(At^2+(4A+B)t+(2A+2B)\\right)\\cdot e^t\n\\end{array}\\right."
Substitute in the original equation
"2\\left(At^2+(4A+B)t+(2A+2B)\\right)\\cdot e^t-\\\\[0.3cm]\n-3\\left(At^2+(2A+B)t+B\\right)\\cdot e^t+\\left(At^2+Bt\\right)\\cdot e^t=t\\cdot e^t\\\\[0.3cm]\n(2A-3A+A)t^2+(2(4A+B)-3(2A+B)+B)t+\\\\[0.3cm]\n+(2(2A+2B)-3B)=t\\\\[0.3cm]\n0\\cdot t^2+(2A)\\cdot t+(4A+B)=t\\longrightarrow\\\\[0.3cm]\n\\left\\{\\begin{array}{l}\n2A=1\\\\[0.3cm]\n4A+B=0\n\\end{array}\\right.\n\\longrightarrow\n\\left\\{\\begin{array}{l}\nA=\\displaystyle\\frac{1}{2}\\\\[0.3cm]\nB=-4A=-2\n\\end{array}\\right."
Conclusion,
"\\boxed{f_{par}(t)=\\left(\\frac{t^2}{2}-2t\\right)\\cdot e^t}"
General solution,
"\\boxed{f(t)=C_1\\cdot e^t+C_2\\cdot e^{t\/2}+\\left(\\frac{t^2}{2}-2t\\right)\\cdot e^t}"
The constants are determined from the initial conditions
"f(0)=1=C_1\\cdot e^0+C_2\\cdot e^{0\/2}+\\left(\\frac{0^2}{2}-2\\cdot0\\right)\\cdot e^0\\\\[0.3cm]\n\\boxed{C_1+C_2=1}\\\\[0.3cm]\nf'(t)=C_1\\cdot e^t+\\frac{C_2}{2}\\cdot e^{t\/2}+(2t-2)\\cdot e^t+\\left(\\frac{t^2}{2}-2t\\right)\\cdot e^t\\\\[0.3cm]\nf'(0)=\\frac{3}{2}=C_1\\cdot e^0+\\frac{C_2}{2}\\cdot e^{0\/2}+(2\\cdot0-2)\\cdot e^0+\\left(\\frac{0^2}{2}-2\\cdot0\\right)\\cdot e^0\\\\[0.3cm]\n\\boxed{C_1+\\frac{C_2}{2}-2=\\frac{3}{2}}"
It remains to solve the system of equations
"\\left\\{\\begin{array}{l}\nC_1+C_2=1\\\\[0.3cm]\n\\left.C_1+\\displaystyle\\frac{C_2}{2}-2=\\displaystyle\\frac{3}{2}\\right|\\times(2)\n\\end{array}\\right.\\longrightarrow\\left\\{\\begin{array}{l}\nC_2=1-C_1\\\\[0.3cm]\n2C_1+C_2-4=3\\end{array}\\right.\\longrightarrow\\\\[0.3cm]\n\\left\\{\\begin{array}{l}\nC_2=1-C_1\\\\[0.3cm]\n2C_1+1-C_1-4=3\\end{array}\\right.\\longrightarrow\n\\left\\{\\begin{array}{l}\nC_2=-5\\\\[0.3cm]\nC_1=6\\end{array}\\right."
Conclusion, solution of IVT is
"\\boxed{f(t)=6\\cdot e^t-5\\cdot e^{t\/2}+\\left(\\frac{t^2}{2}-2t\\right)\\cdot e^t}"
ANSWER
"f(t)=6\\cdot e^t-5\\cdot e^{t\/2}+\\left(\\frac{t^2}{2}-2t\\right)\\cdot e^t"
Comments
Leave a comment